English senior students' gramatical competencies at Centro Regional Universitario de Veraguas (CRUV) - Gallego Zapata, Jhon Esteban
General objective: To examine the grammatical competencies, senior students of the English careerat Centro Regional Universitario de Veraguas handle after four years of exposure to the languaje. Specific objetives: To identify the strenghts and weaknesses of seniors in the typs of sentences, clauses, and phrases. To detemine the proper recognition of English modals by seniors. To identify the proper application of verbs in different activa and passive sentences. To determine the level of aplication of conditional markers in English sentences.